2013
DOI: 10.3389/fonc.2013.00028
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric glioma stem cells: biologic strategies for oncolytic HSV virotherapy

Abstract: While glioblastoma multiforme (GBM) is the most common adult malignant brain tumor, GBMs in childhood represent less than 10% of pediatric malignant brain tumors and are phenotypically and molecularly distinct from adult GBMs. Similar to adult patients, outcomes for children with high-grade gliomas (HGGs) remain poor. Furthermore, the significant morbidity and mortality yielded by pediatric GBM is compounded by neurotoxicity for the developing brain caused by current therapies. Poor outcomes have been attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 150 publications
(187 reference statements)
0
21
0
Order By: Relevance
“…18 Novel and specific therapies currently being investigated for pediatric high-grade glioma include small-molecule inhibitors of epidermal growth factor receptor, platelet-derived growth factor receptor, histone deacetylase, the Ras/AKT pathway, telomerase, integrin, insulinlike growth factor receptor, and ,-secretase, as well as immunotherapy such as vaccines and virotherapy (converting viruses into therapeutic agents). 49,50 Recurrent high-grade glioma carries a dismal prognosis.…”
Section: High-grade Gliomasmentioning
confidence: 99%
“…18 Novel and specific therapies currently being investigated for pediatric high-grade glioma include small-molecule inhibitors of epidermal growth factor receptor, platelet-derived growth factor receptor, histone deacetylase, the Ras/AKT pathway, telomerase, integrin, insulinlike growth factor receptor, and ,-secretase, as well as immunotherapy such as vaccines and virotherapy (converting viruses into therapeutic agents). 49,50 Recurrent high-grade glioma carries a dismal prognosis.…”
Section: High-grade Gliomasmentioning
confidence: 99%
“…However, the effectiveness of oHSVs in patients has not lived up to the expectations generated from the results observed in preclinical studies. 19 Combing oHSV with chemotherapeutic agents presents an opportunity to increase oncolytic activity by either bolstering virus replication or suppressing systemic innate immune responses that can lead to rapid virus clearance. 20 , 21 Despite augmenting virus replication, combination of oncolytic viral therapy with chemotherapy has only been well tolerated with few dose limiting toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, the tumor microenvironment, particularly as it relates to the potential contribution of immune suppression, heterogeneity of cells, and, potentially, GSCs, underscores the nature of the problem. Previous studies have suggested that GSCs are susceptible to treatment with oncolytic HSV (12,13). Until this study, syngeneic models of GSCs were sparse, and none that were suitable for examination of oHSV existed.…”
Section: Approaches To Treatmentmentioning
confidence: 99%